KEPENTINGAN AUSTRALIA MENJUAL URANIUM KE INDIA TAHUN 2011 - Azahari Syafril; Yessi Olivia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This research is purposed to examine carefully the main interest of Australiafrom uranium selling to India in 2011. Also describe the benefit from this bilateralcooperation for the both country. The reasons which prompted Australia to cooperatewith India and the benefits to be gained by Australia. The study also will explain theprocess from the beginning and cooperative relations between Australia and India onuranium’s selling.Keywords : National Interest, Export, Bilateral Cooperation, Nuclear Non-ProliferationTreaty.